Introducing Exploratory Teaching in Preservice Teacher Education Through Lesson Study - Nicole Duarte; João Pedro da Ponte; Filipa Faria (Education Sciences)
In exploratory teaching, the pupils learn from their work on tasks that aim to introduce new concepts, procedures, representations and mathematical ideas. Lesson study, with its focus on teachers’ collaborative and reflective work around issues of pupil learning, is a powerful formative process that may be used in preservice teacher education, sustaining an exploratory teaching approach. In this article, we present a lesson study experience in preservice teacher education, addressing the case of a preservice teacher who is preparing to teach in grades 1–6. Our aim is to identify what key aspects of knowledge of teaching practice does the preservice teacher use when preparing and leading an exploratory lesson during her participation in a lesson study. Our methodology is qualitative, with data collected from the lesson study sessions and the collection of documents produced during the lesson study work, and the data are analysed using a model that presents the key aspects of knowledge of teaching practice. The results show that the structure and the activities carried out in the lesson study, such as designing the lesson, selecting the task and anticipating questions to be posed to pupils, promoted the use of the preservice teacher’s didactic knowledge regarding the phases of an exploratory lesson.